Temperature dependent material behaviour of Inconel steel 625 - Tan, Dillon Kheng Jin (Nanyang Technological University, 2021)
This report explores and studies the effect of temperature on the mechanical properties of the nickel based superalloy, Inconel 625 and carbon steel X60. Tension tests will be performed on the samples at room temperature and design temperatures and the results will be recorded for future findings and industrial applications. Tensile testing is destructive mechanical test which is commonly used to determine mechanical properties of a material such as its yield strength, ultimate tensile strength, elasticity and toughness. In the experiments conducted in this project, the Shimadzu AG-X Plus 50kN Universal Testing Machine is used to carry the tension test. The objective of this report is to obtain the stress-strain relationship of the metals mentioned in accordance to international standards of testing and to examine the effect of temperature on the above-mentioned mechanical properties of the metals. The fabrication of the specimens in the experiments were provided for by DNV, a world-renowned classification society delivering testing, certification and technical advisory. The dimensions of the provided specimen have been altered to comply with the standard, ASTM A370 – 20: Standard Test Methods and Definitions for Mechanical Testing of Steel Products. This report will be useful of future reference on tensile testing on Inconel 625 and carbon steel X60. Furthermore, recommendations for future work will be discussed for the improvement of similar experiments.